Strategi Guru PAI dalam Meningkatkan Pengamalan Beragama Siswa di SMA Negeri 3 Padang Panjang (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to identify the strategies implemented by Islamic Religious Education (PAI) teachers to enhance students’ religious practice at SMA Negeri 3 Padang Panjang. The research employed a descriptive qualitative method, collecting data through interviews and documentation. The findings reveal that PAI teachers’ strategies include giving reprimands, advice, and warnings; guiding students through religious activities such as Quran memorization (tahfiz), Islamic student organizations (rohis), congregational prayers, and other worship practices; and collaborating with parents and fellow teachers. Supporting factors include the encouragement provided by the school and parents, while inhibiting factors involve students’ lack of awareness and their family background.